2016
DOI: 10.1080/02643294.2016.1179179
|View full text |Cite
|
Sign up to set email alerts
|

Wh-questions and passive sentences in non-fluent variant PPA and semantic variant PPA: Longitudinal findings of an anagram production task

Abstract: Using an anagram task, we investigated longitudinal syntactic production by individuals with semantic variant primary progressive aphasia (svPPA) and non-fluent variant PPA (nfvPPA), compared to controls. The accuracy of the production of active and passive, and reversible and non-reversible sentences, as well as of wh- questions was compared across the three groups. Results showed a different pattern of syntactic impairment across the two patient groups. The nfvPPA group showed difficulty with wh- questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In fact, sentence comprehension can be impaired in the progression of PPA-S, although semantic dysfunction is always the prominent deficit in these patients ( 21 , 43 , 70 ) (refer to Thompson and Mack ( 18 ) for a review). In a longitudinal study, Cupit et al ( 105 ) found significant differences in TROG performance between APP-NF/A and APP-S in the first assessment but not on follow-up, demonstrating the decline of PPA-S in this ability as the disease progresses. Therefore, the lack of differentiation in overall scores between PPA subgroups may reflect the progression of disease in some patients with PPA-S.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sentence comprehension can be impaired in the progression of PPA-S, although semantic dysfunction is always the prominent deficit in these patients ( 21 , 43 , 70 ) (refer to Thompson and Mack ( 18 ) for a review). In a longitudinal study, Cupit et al ( 105 ) found significant differences in TROG performance between APP-NF/A and APP-S in the first assessment but not on follow-up, demonstrating the decline of PPA-S in this ability as the disease progresses. Therefore, the lack of differentiation in overall scores between PPA subgroups may reflect the progression of disease in some patients with PPA-S.…”
Section: Discussionmentioning
confidence: 99%
“…There is a bulk of studies indicating that sentences formed by syntactic movement are challenging for speakers with agrammatic aphasia [8] and nf/a PPA [9,10], whose primary linguistic deficit is of a syntactic nature. For example, Thompson et al [10] have shown that speakers with stroke-induced agrammatic aphasia and speakers with agrammatic PPA had comparable performance in sentence production and comprehension.…”
Section: Syntactic Complexity and Its Importance As A Measure Of Ling...mentioning
confidence: 99%
“…Some studies failed to show a duration of disease effect. Cupit et al [9] addressed the issue of decline in language performance in svPPA using an anagram task eliciting the production of active and passive sentences as well as wh-questions (e.g., Who is the boy pushing?) in three different time points.…”
Section: Syntactic Abilities In Svppa Ii: Clinical Factors and Neurop...mentioning
confidence: 99%